Extraocular muscle positions in anterior plagiocephaly: V-pattern strabismus explained using geometric mophometrics. Issue 8 (6th November 2019) - Touzé, Romain; Heuzé, Yann; Robert, Matthieu P.; Brémond-Gignac, Dominique; Roux, Charles-Joris; James, Syril; Paternoster, Giovanna; Arnaud, Eric; Khonsari, Roman Hossein
Abstract : Introduction: Ophthalmological involvement in anterior plagiocephaly (AP) due to unicoronal synostosis (UCS) raises management challenges. Two abnormalities of the extraocular muscles (EOM) are commonly reported in UCS without objective quantification: (1) excyclorotation of the eye and (2) malposition of the trochlea of the superior oblique muscle. Here we aimed to assess the positions of the EOM in AP, using geometric morphometrics based on MRI data. Materials and methods: Patient files were listed using Dr WareHouse, a dedicated big data search engine. We included all patients with AP managed between 2013 and 2018, with an available digital preoperative MRI. MRIs from age-matched controls without craniofacial conditions were also included. We defined 13 orbital and skull base landmarks in order to model the 3D position of the EOM. Cephalometric analyses and geometric morphometrics with Procrustes superimposition and principal component analysis were used with the aim of defining specific EOM anomalies in UCS. Results: We included 15 preoperative and 7 postoperative MRIs from patients with UCS and 24 MRIs from age-matched controls. Cephalometric analyses, Procrustes superimposition and distance computations showed a significant shape difference for the position of the trochlea of the superior oblique muscle and an excyclorotation of the EOM. Conclusions: Our results confirm that UCS-associated anomalies of the superior oblique muscle function are associated with malposition of its trochlea in the roof of the orbit. This clinical anomaly supports the importance of MRI imaging in the surgical management of strabismus in patients with UCS.